Heavy metal toxicity in Buriganga river alters the immunology of Nile tilapia (Oreochromis niloticus L) - Zakir Hossain (Elsevier, 2021)
The objective of the current study was to evaluate the biochemical and immunological responses of tilapia, Oreochromis niloticus due to heavy metals pollution. Histomorphological alterations in the liver and kidney suggested tissue damages due to this polluted water exposure. The brain acetylcholinesterase (AChE) as an indicator of neurotoxicity was significantly (P < 0.01) decreased after 10 days exposure of fish to heavy metal contained river water, while plasma glutamate oxalacetate transaminase and plasma glutamate pyruvate transaminase were significantly increased (P < 0.01). Moreover, superoxide dismutase, catalase, glutathione peroxidase, glutathione S-transferase enzyme activities, as well as reduced glutathione and malondialdehyde levels were significantly increased in heavy metals contained river water treated fish compared to the control. Additionally, glucose level and blood serum Ca2+ concentrations were significantly (P < 0.01) decreased in fish exposed to heavy metal contained river water compared to the control. Hematological indices such as Hemoglobin, RBC, WBC, MCV etc. of polluted river water treated fish were significantly (P < 0.01) different in comparison to that of control fish. The cytokines i.e. IL-1β, IL-6, and TNF-α level were significantly (P < 0.01) increased in the fish exposed to heavy metals contained river water in comparison to that of control fish. The present findings explored the detrimental effects of heavy metal contained river water on fish at biochemical and immunological levels.